SEANGKONAN DAN RELEVANSINYA DENGAN PRINSIP KAFA’AH DALAM PERKAWINAN ISLAM - Gandhi Liyobra Indra (Institut Agama Islam Negeri Metro, 2022)
The purpose of writing this article is to analyze the relevance of seangkonan in Lampung pubian traditional marriages with the principle of kafa'ah in Islamic marriages. This is based on the fact that in the Lampung Pubian tradition, if someone who is going to marry one of the couples does not come from the Lampung Pubian tribe, the person concerned must follow the Seangkonan tradition. This tradition is a condition for the candidate to be recognized according to custom and marry according to custom. If you do not follow this tradition, the person concerned will be subject to sanctions. This research is a field research that is descriptive qualitative in nature with the main data coming from interviews. The results of Seangkonan in the context of efforts to equalize positions are in line with the concept of kafa'ah in Islam. This is because seangkonan in the Lampung pubian custom is an attempt to recognize an equal position. Only in a formal legal context, there is nothing formal that underlies the permissibility of seangkonan in the Lampung pubian custom as one of the things that must be done by couples who are about to get married. This is precisely what causes harm.